Pengaruh E-Commerce, Penggunaan Sistem Informasi Akuntansi, Dan Ilmu Kewirausahaan Terhadap Minat Mahasiswa Akuntansi Untuk Berwirausaha - Alvi Nabilah; Salsabilla Ronardi; Queen Shakira Azzahra; Fitrah Maharani; Siti Rodiah (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to provide additional empirical evidence to understand whether accounting students’ entrepreneurial interest is enhanced by e-commerce, entrepreneurship science, and accounting information systems. Quantitative research is used in this type of research. The data analysis technique used is Multiple Linear Regression. The data collection technique used by researchers is by distributing online questionnaires to 50 Accounting students class of 2021 Regular A, Faculty of Economics and Business, Muhammadiyah University of Riau and processing them using SPSS 26. The results of the research show that partially E-commerce and Accounting Information Systems do not have a significant effect on interest in entrepreneurship, while entrepreneurship knowledge has a significant effect on interest in entrepreneurship.